Phát triển kỹ năng nói Tiếng Anh cho sinh viên thông qua hoạt động tranh luận - Mai, Lan Anh (Hiệp hội thiết bị giáo dục Việt Nam, 2023)
Debate is one of effective strategies that encourages thinking skills and also offers motivating contexts for students to communicate with one anotherThis study aimed at implementing the debate technique to improve the third -year majors' speaking abilityThe study applied the classroom action research method which consisted of 3 cyclesAn observation checklist and field notes were used to collect the data. The subjects of the study were 60 third-year majors at Hanoi University of CultureThe results of the study showed that the debate technique improved students' speaking ability in making questions and giving explanations.